Inside the mind of Adolf Hitler - Stewart, David ([Australia] : BBC, 2005)
At the eight of World War II, with the future of the world still hanging in the balance, understanding enemy thinking wassupreme importance. The Americans tried to predict how it would all end by getting inside the mind of one man who could determine the final outcome - Adolf Hitler. The top-secret psychological profile that the American secret service produced has been locked away for decades.
Title from title screen
Narrator: Michael Praed
dvd format
Keywords: Hitler, Adolf, -- 1889-1945 -- Psychology; Hitler, Adolf, -- 1889-1945 -- Mental health; Heads of state -- Germany -- Psychology; Germany -- Politics and government -- 1933-1945